A study on the insecticidal properties of Lansium domesticum peeling extracts - Taban, Evelyn Danguilan E. (Animo Repository, 1984)
The insecticidal properties of the crude extracts of the peelings of lanzones (Lansium domesticum Correa) on cockroaches is studied in this thesis. The solvents used in the exhaustive extractions were petroleum ether, acetone, methanol and water. The crude petroleum ether extract showed the highest insecticidal activity. Benzene and chloroform were efficient as developing solvent systems in separating the components. One of the active components of the petroleum ether extract was separated and isolated by column chromatography using benzene as eluant. Fraction K, which has only one spot as revealed by the TLC was further characterized by NMR and IR spectroscopy. The NMR revealed the presence of hydrocarbons and ketones as shown by the peaks at high field, i.e., near the peak at s = 0.70 to 4.70. The IR spectrum confirms these compounds.